2014
DOI: 10.1523/jneurosci.3635-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-Specific Modulation of GABAergic Synaptic Transmission by TRPV1 Channels in the Dentate Gyrus

Abstract: The transient receptor potential TRPV1 or vanilloid receptor is a nonselective ligand-gated channel highly expressed in primary sensory neurons where it mediates nociception. TRPV1 is also expressed in the brain where its activation depresses excitatory synaptic transmission. Whether TRPV1 also regulates inhibitory synapses in the brain is unclear. Here, using a combination of pharmacology, electrophysiology, and an in vivo knockdown strategy, we report that TRPV1 activation by capsaicin or by the endocannabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 54 publications
1
45
0
2
Order By: Relevance
“…Stimulation of the mtCB1R leads to inhibition of mitochondrial oxidative phosphorylation and ATP production in the mitochondria and can modulate neurotransmitter release through mechanisms that are still unknown (indicated by the question mark) 146 . AEA can also activate the postsynaptic non-selective cation channel transient receptor potential cation channel subfamily V member 1 (TRPV1) 71,72,178,179 , leading to an increase in postsynaptic current, whereas 2-AG can also stimulate postsynaptic GABA A receptors 180 . On depolarization of the postsynaptic terminal, for example, by activation of metabotropic receptors (metabotropic glutamate receptor 1 (mGluR1; also known as GRM1), mGluR5, muscarinic receptor type 1 (M 1 ) or M 2 ) 8,14 , 2-AG is postsynaptically synthesized ‘on-demand’ by diacylglycerol lipase-α (DAGLα) in dendritic spines of excitatory synapses 181183 .…”
Section: Figurementioning
confidence: 99%
“…Stimulation of the mtCB1R leads to inhibition of mitochondrial oxidative phosphorylation and ATP production in the mitochondria and can modulate neurotransmitter release through mechanisms that are still unknown (indicated by the question mark) 146 . AEA can also activate the postsynaptic non-selective cation channel transient receptor potential cation channel subfamily V member 1 (TRPV1) 71,72,178,179 , leading to an increase in postsynaptic current, whereas 2-AG can also stimulate postsynaptic GABA A receptors 180 . On depolarization of the postsynaptic terminal, for example, by activation of metabotropic receptors (metabotropic glutamate receptor 1 (mGluR1; also known as GRM1), mGluR5, muscarinic receptor type 1 (M 1 ) or M 2 ) 8,14 , 2-AG is postsynaptically synthesized ‘on-demand’ by diacylglycerol lipase-α (DAGLα) in dendritic spines of excitatory synapses 181183 .…”
Section: Figurementioning
confidence: 99%
“…2010), and to reduce perisomatic GABAergic inputs (Chávez et al . 2014). In the hippocampus proper, Gibson et al .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, while Cavanaugh et al (2011) have suggested that CRs are the only hippocampal neuronal type expressing TRPV1, other studies indicate a more widespread expression, including several other neuronal types (i.e. pyramidal cells, GABAergic interneurons, and granule cells; see Toth et al 2005;Cristino et al 2006;Gibson et al 2008;Chávez et al 2010Chávez et al , 2014Puente et al 2015;Canduela et al 2015;Lee et al 2015;Eguchi et al 2016;Hurtado-Zavala et al 2017; see also review by Kauer & Gibson, 2009). Thus, application of capsaicin might trigger some form of network activity, which would result, indirectly, in responses in CRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMDA receptor mediated calcium entry and CaN activation was further shown to decrease surface α2‐containing receptors during in vitro epileptiform activity by live‐cell imaging techniques (Eckel et al, ). Activation of the transient receptor potential cation channel subfamily V member 1 also appears to cause GABA A R endocytosis in the dentate gyrus of rodents dependent on calcium influx, CaN, and dynamin‐activity (Chavez et al, ). In addition, inflammation and release of the proinflammatory cytokine tumor necrosis factor‐α (TNFα) stimulates GABA A R internalization (α1/2/5, β3, γ2) in a CaN‐independent pathway in cultured hippocampal neurons (Pribiag and Stellwagen, ).…”
Section: Gabaar Internalization Recycling and Lysosomal Degradationmentioning
confidence: 99%